(untitled) (Italian Journal of Public Health, 2012)
Background: in 2009 a novel infective agent, a(H1n1), was recognized by the World Health organization (WHo) as a pandemic virus. Like most European countries, Italy experienced a single pandemic wave during fall-winter 2009. The objective of our study was to evaluate the news reports and the representation of the a(H1n1) pandemic in the Italian newspapers both quantitatively and qualitatively. Methods: from april 24th, 2009 to February 28th, 2010, seven national newspapers were monitored for the quantitative reporting of a(H1n1). In a three month sample period, reports were evaluated quali- tatively by considering their front page presence, tones used for headlines, and images and figures dedicated to the topic. Results: in a ten month window, a total of 1220 articles were published. The reporting period showed four peaks and one hollow, with a similar pattern for all the newspapers. during the three-month sample period, we found a total of 382 articles, 98.4% of which appeared on front pages, 33.8% of which contained headlines using alarming tones, and 47.8% which contained info-graphic elements. Conclusions: the a(H1n1) 2009 pandemic in Italy was mild; nonetheless, newspapers devoted great attention to the new influenza and used alarmist tones. In similar situations, there are several areas where scientists should play a greater role. scientists should support journalists in understanding scientific issues and help them translate scientific information into news items. scientists should also help to contain the anxiety aroused in lay people by a pandemic, and support vaccination efforts dedicated to it....